University teachers' attitudes towards ICTs and the use of virtual environments during the COVID-19 pandemic - Ruiz-Aquino, Mely (2021)
The aim of this research was to determine the relationship between the attitude towards information and communication technologies (ICTs) and the use of virtual teaching-learn-ing environments on the part of teachers at the University of Huánuco (Peru) during the COVID-19 pandemic. The study was based on the positivist paradigm and consisted of a quantitative approach, analytical method and correlational design. The sample comprised 210 teachers to whom the teacher’s attitude towards ICTs scale and the questionnaire on the use of virtual teaching-learning environments were applied. As a result, a positive (rs= .53) and significant (p = .00) relationship was detected between both variables. It was concluded that the use of virtual environments was positively and significantly related with the attitudes towards ICTs of the university teachers in the sample; in other words, the more positive the attitude towards ICTs, the greater the use of virtual environments.